Peran Notaris dalam Memberikan Kepastian Hukum Terhadap Hak Mewaris Penderita Ambiguous Genitalia berdasarkan Hukum Waris Islam - Taris Pohan, Naufal; Suprayitno; Sembiring, Rosnidar (AL-SULTHANIYAH, 2025)
In society, some individuals are born with genitalia that do not conform to typical male or female characteristics, a condition medically referred to as ambiguous genitalia. This study adopts a normative juridical approach, utilizing statutory and conceptual approaches. Legal materials were obtained through literature reviews and interviews and were analyzed using grammatical interpretation and legal argumentation techniques, including analogy. The findings indicate that, from the perspective of Islamic law, ambiguous genitalia can be classified analogously to the condition of khunsa. A notary may draft a Certificate of Inheritance Rights or an Act of Separation and Distribution of Inheritance as long as all heirs mutually agree to resolve the matter outside the court. However, if the heirs cannot reach a consensus, the notary may direct them to submit an inheritance determination request to the local Religious Court. In drafting such legal documents, a notary may act as a legal innovator to address legal gaps not yet regulated by statutory provisions, provided that all parties involved agree.